Development of novel benzofuran-isatin conjugates as potential antiproliferative agents with apoptosis inducing mechanism in Colon cancer - Wagdy M. Eldehna; Rofaida Salem; Zainab M. Elsayed; Tarfah Al-Warhi; Hamada R. Knany; Rezk R. Ayyad; Thamer Bin Traiki; Maha-Hamadien Abdulla; Rehan Ahmad; Hatem A. Abdel-Aziz; Radwan El-Haggar (Taylor & Francis Group, 2021)
In the current work, a new set of carbohydrazide linked benzofuran-isatin conjugates (5a-e and 7a-i) was designed and synthesised. The anticancer activity for compounds (5b-d, 7a, 7b, 7d and 7g) was measured against NCI-55 human cancer cell lines. Compound 5d was the most efficient, and thus subjected to the five-dose screen where it showed excellent broad activity against almost all tested cancer subpanels. Furthermore, all conjugates (5a-e and 7a-i) showed a good anti-proliferative activity towards colorectal cancer SW-620 and HT-29 cell lines, with an excellent inhibitory effect for compounds 5a and 5d (IC50 = 8.7 and 9.4 µM (5a), and 6.5 and 9.8 µM for (5d), respectively). Both compounds displayed selective cytotoxicity with good safety profile. In addition, both compounds provoked apoptosis in a dose dependent manner in SW-620 cells. Also, they significantly inhibited the anti-apoptotic Bcl2 protein expression and increased the cleaved PARP level that resulted in SW-620 cells apoptosis.